Family Welfare and Work Ethos: The Role of Social Capital and Family Resources in North Timor District (International Journal of Scientific Research and Management (IJSRM), 2022)
This study aims to evaluate the effect of Social Capital and Family Resources on Work Ethic which leads to improving the welfare of underprivileged families in North Central Timor district based on the local wisdom of the Dawan community. With the work culture that is owned and the potential for family and kinship relationships as well as the trust that is fostered in the community, it is able to improve family welfare. This study uses a qualitative descriptive method with an associative approach to determine the correlation between variables. The results of the study indicate that: social capital and family resources each have an effect on work ethic. While the work ethic also affects the welfare of the family. The results of this study also found that: social capital and family resources have an influence on family welfare if there is an increase in the work ethic of underprivileged families.